2016
DOI: 10.1038/cti.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human monocytes and derived subsets of macrophages and dendritic cells by the HLDA10 monoclonal antibody panel

Abstract: The mononuclear phagocyte system, consisting of monocytes, macrophages and dendritic cells (DCs), has an important role in tissue homeostasis as well as in eliciting immune responses against invading pathogens. Blood monocytes have been viewed for decades as precursors of tissue macrophages. Although the newest data show that in the steady state resident macrophages of many organs are monocyte independent, blood monocytes critically contribute to tissue macrophage and DC pools upon inflammation. To better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…One candidate could be GM-CSF. Indeed, it has been shown that blood monocytes differentiate to immature Mf-like cells through GM-CSF ex vivo (281,282), a factor that increases in Crohn's disease and UC, particularly in active lesion areas (283). Moreover, GM-CSF can act in concert with IFN-γ and TNF to reprogram blood monocytes into Mfs with an inflammatory profile (284).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…One candidate could be GM-CSF. Indeed, it has been shown that blood monocytes differentiate to immature Mf-like cells through GM-CSF ex vivo (281,282), a factor that increases in Crohn's disease and UC, particularly in active lesion areas (283). Moreover, GM-CSF can act in concert with IFN-γ and TNF to reprogram blood monocytes into Mfs with an inflammatory profile (284).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…Monocytes were further purified from the PBMC fraction using CD14 MACS microbeads (Miltenyi Biotec, Bergisch Gladbach, Germany). Primary macrophages were differentiated from CD14 + monocytes with recombinant human macrophage colony‐stimulating factor (M‐CSF; from Peprotech, Rocky Hill, NJ; 50 ng/ml) as previously described . Following a 7‐day differentiation, macrophages were rested in macrophage serum free medium (Invitrogen), supplemented with 2 mmol/l l ‐glutamine and 2% FCS for 2 days prior to efferocytosis assays.…”
Section: Methodsmentioning
confidence: 99%
“…While IL-2 is mainly expressed in Th cells, IL-15 is constitutively expressed by certain immune cell populations including monocytes, macrophages, and dendritic cells [15]. In the blood, circulating monocytes are recruited to inflamed tissues and can derive to macrophages or dendritic cells [16]. The removal of the inflammatory site due to the arthroplasty could therefore explain the post-operative reduction of peripheral NK cells.…”
Section: Discussionmentioning
confidence: 99%